Hyperspectral remote sensing & spectral signature applications - S.Rajendran and others; Rajendran, S. (New Delhi : New India Pub. Agency, 2009)
Contributed papers presented at the National Seminar on "Hyperspectral Remote Sensing and Spectral Signature Databse Management System", held on February 14-15, 2008 at Annamalai University.
Includes bibliographical references.
Keywords: Remote sensing -- India -- Congresses